A comprehensive study on cellulose nanofibril reinforced polylactic acid 3D printed composites - Bodur, Mehmet Safa; Avci, Ali (ELSEVIER, 2026)
This study comprenhensivly investigates the development and optimization of cellulose nanofibril (CNF)-reinforced polylactic acid (PLA) composite filaments for FDM-based 3D printing through a three-stage approach: printing parameter optimization, composite formulation design, and thermal annealing. First, the effects of infill pattern and layer thickness were assessed using neat PLA. Tensile testing and ANOVA demonstrated that the Line infill pattern and a 0.25-0.30 mm layer thickness provided superior mechanical performance, establishing the baseline printing conditions. Subsequently, CNF was incorporated into PLA at 0.25-3 %wt, together with two coupling agents (SCONA TPPL 1112 and 5112) at 2 and 4 %wt. Filaments were extruded and used to fabricate test specimens. Low CNF contents (0.25 %wt, 0.5 %wt, 1 %wt, 3 %wt) enhanced tensile strength and stiffness, particularly when combined with coupling agents; the 0.25CNF-2CA(1112) formulation achieved the highest improvement, reaching similar to 52 MPa tensile strength and a similar to 60% increase in Young's modulus compared with neat PLA. Higher CNF loadings (>= 1 %wt) led to fiber agglomeration, reduced dispersion, and diminished mechanical properties. Flexural and impact strengths generally decreased at elevated CNF contents due to increased brittleness and reduced interlayer diffusion. The final stage examined thermal annealing of the optimal composite. Annealing at 70-100 degrees C for 30-120 minutes significantly increased crystallinity and stiffness. The best performance was obtained at 100 degrees C for 90 minutes, yielding a tensile strength of similar to 54 MPa and a modulus exceeding 3300 MPa-corresponding to improvements of approximately 28 % and 106 % relative to pure PLA. However, prolonged annealing (120 minutes) caused embrittlement, lowering both strength and ductility. Overall, the results demonstrate that controlled CNF reinforcement, appropriate coupling agents, optimized printing parameters, and moderate thermal annealing synergistically enhance the mechanical and thermal characteristics of CNF/PLA composites, providing a promising route for high-performance bio-based 3D printing materials.
Keywords: CNF/PLA composite filament; Coupling agent; Thermal annealing; Optimization; 3D printing; PLA; POLY(LACTIC ACID); MECHANICAL-PROPERTIES; NANOCRYSTALS; CRYSTALLINITY; MORPHOLOGY; EXTRUSION; Chemistry; Materials Science; Physics